Fatal outcome of anti-MDA5 juvenile dermatomyositis in a paediatric COVID-19 patient: a case report. (2nd January 2021) - Quintana-Ortega, Cristian; Remesal, Agustín; Ruiz de Valbuena, Marta; de la Serna, Olga; Laplaza-González, María; Álvarez-Rojas, Elena; Udaondo, Clara; Alcobendas, Rosa; Murias, Sara
Abstract: Anti-melanoma differentiation-associated gene 5 juvenile dermatomyositis (anti-MDA5 JDM) is associated with high risk of developing rapidly progressive interstitial lung disease (RP-ILD). Here we report an 11-year-old girl with anti-MDA5 JDM and RP-ILD which led to a fatal outcome, further aggravated by SARS-CoV-2 infection. She was referred to our hospital after being diagnosed with anti-MDA5 JDM and respiratory failure due to RP-ILD. On admission, fibrobronchoscopy with bronchoalveolar lavage (BAL) revealed Pneumocystis jirovecii infection so treatment with intravenous trimethoprim-sulfamethoxazole was initiated. Due to RP-ILD worsening, immunosuppressive therapy was intensified using methylprednisolone pulses, cyclophosphamide, tofacitinib and intravenous immunoglobulin without response. She developed severe hypoxemic respiratory failure, pneumomediastinum and pneumothorax, further complicated with severe RP-ILD and cervical subcutaneous emphysema. Three real-time RT-PCR for SARS-CoV-2 were made with a negative result. In addition, she was complicated with a secondary hemophagocytic lymphohistiocytosis and a fourth real-time PCR for SARS-CoV-2 performed in BAS sample was positive. Despite aggressive treatment of RP-ILD due to anti-MDA5 JDM, there was no improvement of respiratory failure in the following days and patient developed refractory septic shock and died. Anti-MDA5 JDM patients with RP-ILD have a poor prognosis with a high mortality rate. For this reason, intensive immunosuppressive therapy is essential including the use of promising drugs such as tofacitinib. COVID-19 in children with underlying health conditions like anti-MDA5 JDM may still be at risk for disease and severe complications.